2019
DOI: 10.1111/jipb.12802
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tillage managements and maize straw returning on soil microbiome using 16S rDNA sequencing

Abstract: Agricultural practices could affect bacterial diversity and community structure by altering soil physical and chemical properties. Straw returning and tillage practices are widely used in agriculture, however, the effects of these agricultural practices on microbiomes are still unclear. In the present study, we compared the 18 bacterial communities of soil with different straw returning and tillage treatment combinations. The V3–V4 regions of the 16S ribosomal RNA were amplified and analyzed by high‐throughput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 43 publications
4
23
0
Order By: Relevance
“…Specifically, the abundances of carbohydrate metabolism pathways, including galactose metabolism, amino sugar and nucleotide sugar metabolism, starch and sucrose metabolism, glyoxylate and dicarboxylate metabolism, changed significantly when straws were added. This result was similar to those observed by Xia et al (2019) [44] who found that the pathways involved in metabolism of macromolecular compounds, such as amino sugars and nucleotide sugars metabolism, were more abundant in treatment without straw than that in treatment with straw. In this work ( Figure S2), we found that there were 5, 9 and 23 functional pathways showing significant changes in treatment SD, BC and SC, respectively, compared to the control of CK.…”
Section: Effects Of Straw Input On Microbial Community Compositionsupporting
confidence: 92%
“…Specifically, the abundances of carbohydrate metabolism pathways, including galactose metabolism, amino sugar and nucleotide sugar metabolism, starch and sucrose metabolism, glyoxylate and dicarboxylate metabolism, changed significantly when straws were added. This result was similar to those observed by Xia et al (2019) [44] who found that the pathways involved in metabolism of macromolecular compounds, such as amino sugars and nucleotide sugars metabolism, were more abundant in treatment without straw than that in treatment with straw. In this work ( Figure S2), we found that there were 5, 9 and 23 functional pathways showing significant changes in treatment SD, BC and SC, respectively, compared to the control of CK.…”
Section: Effects Of Straw Input On Microbial Community Compositionsupporting
confidence: 92%
“…Averaged across three land uses, the contents of silt, clay and soil dry-stable aggregates ( R 0.25 ) in grassland was highest among all three land uses studies, which is in agree with a previous study by Liu et al 40 . It should be noted that tillage and harvesting practices in arable land and low vegetation coverage in forest land may promote soil erosion and cause the loss of silt and clay contents and the decrease of soil aggregate stability in topsoil 41 , 42 . The alfalfa plants generally have a well-developed root system, which produces more organic matter as the roots decompose.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, high-throughput sequencing technology provides an effective method for studying soil microbial community changes under different conditions. Most studies using high-throughput sequencing demonstrate that soil microbial community diversity and structure composition are influenced by all kinds of cultivation measures, including fertilization management, no-till, cover crops, crop rotation and so on [17][18][19][20][21]. In organic farming, soil microbiological activity is of primary importance as nutrient supply is mainly dependent on the degradation of soil organic matter by soil microorganisms [22].…”
Section: Introductionmentioning
confidence: 99%